A randomized trial of hyperimmune globulin to prevent congenital cytomegalovirus. - Revello, Maria Grazia; Lazzarotto, Tiziana; Guerra, Brunella; Spinillo, Arsenio; Ferrazzi, Enrico; Kustermann, Alessandra; Guaschino, Secondo; Vergani, Patrizia; Todros, Tullia; Frusca, Tiziana; Arossa, Alessia; Furione, Milena; et al. (N Engl J Med, 2014)
BACKGROUND: Congenital infection with human cytomegalovirus (CMV) is a major cause of morbidity and mortality. In an uncontrolled study published in 2005, administration of CMV-specific hyperimmune globulin to pregnant women with primary CMV infection significantly reduced the rate of intrauterine transmission, from 40% to 16%. METHODS: We evaluated the efficacy of hyperimmune globulin in a phase 2, randomized, placebo-controlled, double-blind study. A total of 124 pregnant women with primary CMV infection at 5 to 26 weeks of gestation were randomly assigned within 6 weeks after the presumed onset of infection to receive hyperimmune globulin or placebo every 4 weeks until 36 weeks of gestation or until detection of CMV in amniotic fluid. The primary end point was congenital infection diagnosed at birth or by means of amniocentesis. RESULTS: A total of 123 women could be evaluated in the efficacy analysis (1 woman in the placebo group withdrew). The rate of congenital infection was 30% (18 fetuses or infants of 61 women) in the hyperimmune globulin group and 44% (27 fetuses or infants of 62 women) in the placebo group (a difference of 14 percentage points; 95% confidence interval, -3 to 31; P=0.13). There was no significant difference between the two groups or, within each group, between the women who transmitted the virus and those who did not, with respect to levels of virus-specific antibodies, T-cell-mediated immune response, or viral DNA in the blood. The clinical outcome of congenital infection at birth was similar in the two groups. The number of obstetrical adverse events was higher in the hyperimmune globulin group than in the placebo group (13% vs. 2%). CONCLUSIONS: In this study involving 123 women who could be evaluated, treatment with hyperimmune globulin did not significantly modify the course of primary CMV infection during pregnancy. (Funded by Agenzia Italiana del Farmaco; CHIP ClinicalTrials.gov number, NCT00881517; EudraCT no. 2008-006560-11.).
Keywords: Adult; Amniocentesis; Cytomegalovirus; Cytomegalovirus Infections; Female; Fetal Diseases; Humans; Immunoglobulins; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious